Listeriosis and Listeria monocytogenes in Portugal : from surveillance studies to persistence in food processing plants - Magalhães, Rui Miguel Barros de Sousa (2022)
Listeria monocytogenes is a foodborne pathogen capable of causing severe human disease (listeriosis) when contaminated foods are ingested, particularly in groups at higher risk for listeriosis: the very young, old, immunocompromised individuals and pregnant women. Its ubiquity and ability to adapt and survive under extreme conditions (e.g., refrigeration temperatures, wide pH range, high salt concentrations), makes this pathogen of difficult eradication and control in the food-processing environment. Contaminated readyto- eat foods that support the growth of the pathogen are a major concern. Crosscontamination by the equipment and the general food processing environment is one of the most important sources of food contamination. Some strains may persist in food processing environment over several months/years, while others are only sporadically recovered. Although it is general accepted that particular traits of these strains contribute to their persistence in food processing environment, specific characteristics of strains that confer better survival/adaptation to the food processing environment remain unclear but are essential for planning preventive measures. Previous studies performed in the CBQF (Centro de Biotecnologia e Química Fina – Centre of Biotechnology and Fine Chemistry) demonstrated that strains that caused human listeriosis were isolated from cheeses and the cheese processing plants. The overall goal of this work was to integrate applied research and outreach to augment knowledge and try to define control strategies regarding L. monocytogenes persistence in food processing environment and monitoring the cases of listeriosis in Portugal. Information regarding cases of listeriosis, and when available the isolate that caused the disease, have been collected from the main hospitals in Portugal between 2008 and 2012. A total of 203 cases of listeriosis were detected. The annual incidence rate observed ranged from 0.2 to 0.7 cases per 100,000 inhabitants. The mean age of the nonmaternal/neonatal (non-MN) cases with documented age was 59 years, and 46.4% occurred in patients aged over 65 years. Clinical isolates were characterized by genoserotyping, resistance to arsenic and cadmium and DNA macrorestriction analysis by pulsed field gel electrophoresis. The minimal inhibitory concentrations of antimicrobials was also determined. Several clusters of isolates presenting different geographic and time distributions were detected. The incidence of antibiotic-resistant isolates of L. monocytogenes was low but significantly higher than in previous years (2003-2007). This study, involving 25 national hospitals, led to the detection of an outbreak that occurred between March 2009 and February 2012. Of the 30 cases of listeriosis reported, 27 were in the Lisbon and Vale do Tejo region. The case fatality rate was 36.7%. All cases were caused by molecular serogroup IVb isolates indistinguishable by pulsed-field gel electrophoresis and ribotype profiles. Collaborative investigations with the national health and food safety authorities identified cheese as the probable source of infection, traced to a processing plant. A previous longitudinal study carried by our research team identified persistence in from two cheese processing plants. A selected group of 41 persistent and non-persistent L. monocytogenes isolates was assembled for this study. The effect of different conditions, including temperature (37 ºC, 22 ºC, and 4 ºC), NaCl concentrations (2.5%, 4%, and 8%), and acidity (pH = 5), on the growth response of persistent and non-persistent isolates of L. monocytogenes was determine; the resistance to two common sanitizers (benzalkonium chloride and hydrogen peroxide) was also investigated. Results suggest that persistent strains may be more adapted to grow under stressful conditions frequently encountered in food processing environments, like 22 ºC, 2.5%, 4% and 8% NaCl, and at pH 5, than nonpersistent strains. No relation between persistence and resistance to the tested sanitizers was found. For the group of 41 isolates a new selection of a six persistent and seven nonpersistent strains isolated from the same processing plants were evaluated for biofilm formation in stainless steel, silicon rubber, and polyvinyl chloride (PVC) coupons; a microplate titer assay was also carried out. Persistent strains produced more biofilm than non-persistent strains in stainless steel and silicon rubber surfaces; but no significant differences were observed in PVC. In the polystyrene microtiter plate assay stained with cristal violet no evidence was found that persistent strains have higher ability to form biofilm than non-persistent strains, and no correlation was identified between biofilm formation in the microtiter plate and in the three other surfaces tested. The continuous subtyping of isolates is essential and the study of persistence of L. monocytogenes in food processing plants is important to develop new and more efficient strategies for control of this pathogen.